PDE5 and PDE10 inhibition activates cGMP/PKG signaling to block Wnt/β-catenin transcription, cancer cell growth, and tumor immunity. Issue 8 (August 2020) - Piazza, Gary A.; Ward, Antonio; Chen, Xi; Maxuitenko, Yulia; Coley, Alex; Aboelella, Nada S.; Buchsbaum, Donald J.; Boyd, Michael R.; Keeton, Adam B.; Zhou, Gang
Highlights: NSAIDs have anticancer activity but have toxicities resulting from COX inhibition. The mechanism of NSAID anticancer activity may not require COX inhibition. PDE5 and PDE10 are overexpressed in tumors and essential for cancer cell growth. Novel sulindac derivatives targeting PDE5 or PDE10 have strong anticancer activity. Abstract : Although numerous reports conclude that nonsteroidal anti-inflammatory drugs (NSAIDs) have anticancer activity, this common drug class is not recommended for long-term use because of potentially fatal toxicities from cyclooxygenase (COX) inhibition. Studies suggest the mechanism responsible for the anticancer activity of the NSAID sulindac is unrelated to COX inhibition but instead involves an off-target, phosphodiesterase (PDE). Thus, it might be feasible develop safer and more efficacious drugs for cancer indications by targeting PDE5 and PDE10, which are overexpressed in various tumors and essential for cancer cell growth. In this review, we describe the rationale for using the sulindac scaffold to design-out COX inhibitory activity, while improving potency and selectivity to inhibit PDE5 and PDE10 that activate cGMP/PKG signaling to suppress Wnt/β-catenin transcription, cancer cell growth, and tumor immunity.